A Qualitative Analysis of the Experience and Impact of Killing in Hand‐to‐Hand Combat. Issue 4 (26th August 2014) - Jensen, Peter R.; Simpson, Duncan
Abstract: A growing body of research suggests that killing during military combat is closely associated with posttraumatic stress disorder (PTSD), as well as a number of other adverse mental health related conditions (e.g., dissociative experiences, violent behavior, functional impairment). This article provides first‐person perspectives on the experiences and impact of killing by service members with the goal of expanding our understanding of the impact of taking a life during war. In audio‐recorded phenomenological interviews, 9 service members described their experiences and the subsequent impact of killing during hand‐to‐hand combat. A description, supported by participant quotations, was constructed to represent the participants' experiences. Results suggest the experience and aftermath of taking a life in hand‐to‐hand combat was disturbing, psychologically stressful, and necessitated some form of coping after the event. Service members who killed in hand‐to‐hand combat viewed their actions as necessary to preserve their life and that killing in hand‐to‐hand combat was more emotionally taxing than killing by shooting. Our findings may help to improve providers' understanding of service members' first‐person experiences of killing in hand‐to‐hand combat and thus provide the basis for the development of a connected and genuine relationship with such military clients.